Estimasi Tinggi Badan Berdasarkan Panjang Telapak Tangan dan Panjang Telapak Kaki - Santosa, Novian Anindito; Tamtomo, Didik Gunawan; Suwandono, Adji (Nexus Kedokteran Klinik, 2014)
Background: Body height measurement is one of forensic identification examinations. One of evidence that probably found in forensic cases is hand length or foot length. This research aimed to the know correlation between hand length and body height, foot length and body height, and also hand length and foot length with body height. Methods: This research was descriptive analytic with cross-sectional study design. The research was held in Faculty of Medicine Universitas Sebelas Maret with 40 samples of students which consisted of 24 males and 16 females. Independent variable of this research werehand and foot length. Hand length was measured with caliper, foot length was measured with plan A4 paper and ruler. Dependent variable of this research was body height estimation which was measured with microtoise. Samples obtained were measured height, hand length and foot length. The result obtained was tested with double linear regression test. Results: The statistical analysis result for regression test partially obtained that right hand length had correlation score (r) 0,971 (p=0,000), left hand length had correlation score (r) 0,968 (p=0,000),right foot length had correlation score (r) 0,975 (p=0,000), left foot length had correlation score (r) 0,973 (p=0,000). While the result of double linear regression test had correlation score (r) 0,999 (p=0,000). Conclusions: There was correlation between hand length and body height, foot length and body height, and also hand length and foot length with body height. Keywords: Body height,hand length Â foot length. Â